Flexible Capturing Application for Enhanced Generation of EPCIS Events - Fengjuan Jia; Seungwoo Jeon; Bonghee Hong; Joonho Kwon; Yoon-sik Kwak (International Journal of Distributed Sensor Networks)
Radio frequency identification (RFID) technology and electronic product code (EPC) technology have been widely used to identify and keep track of physical objects. EPCglobal proposed the EPC network which consists of several components such as application level events (ALE) and EPC information service (EPCIS) to deal with the captured data from different layers. Many studies mostly concentrated on dealing with the RFID tag data in ALE, as well as querying and sharing EPCIS events in EPCIS. However, there is no well-known study on specifying how to generate higher level EPCIS events. The event types and semantic event fields are both uncertain for the capturing application to generate EPCIS events. Therefore, this paper proposes the flexible capturing application (FCA) to solve the problem that the event types and semantic event fields are both uncertain. FCA specifies generation rules about the four EPCIS event types. All the generation rules are matched for the incoming tag data to determine the event types. Event fields are generated with tag data and other sources of data after deciding event types. Thus, FCA can generate EPCIS events arising from supply chain activity. We evaluate our approaches by means of simulation and real experiments. Our experimental results indicate that FCA can be effective in processing EPCIS events data. We conclude with suggestions for future work.